Trinidad and Tobago. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Trinidad and Tobago during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as family farming, nutrition, packaging, labeling, trade, fodder, public policies, innovation, safety through the Codex Alimentarius. Finally, small and medium-sized enterprises and the breeding and production of small ruminants were supported.